Investigation of solvent system for the production of biodiesel from Sludge Palm Oil (SPO) by enzymatic transesterification - Alam, Md. Zahangir; Nasaruddin, Ricca Rahman; Jami, Mohammed Saedi; Uddin , Mohammad Shahab (2013)
Sludge palm oil (SPO) was used to produce biodiesel by direct enzymatic transesterification using locally produced Candida cylindracea lipases from palm oil mill effluent (POME). The solvent system was investigated by comparing the effect of methanol and ethanol. The yield of biodiesel and conversion of free fatty acids (FFAs) into biodiesel for ethanol were higher than the methanol. Ethanol was selected based on the findings of ethanol-to-SPO molar ratio, water content, and additional organic solvent. The optimum ethanol-to-SPO molar ratio was found to be 4:1 while the increasing of water content reduced the activity of the lipases thus it showed lower yield and conversion of biodiesel. It was also found that the addition of n-hexane with 1:1 hexane-to-SPO molar ratio increased the yield of biodiesel and conversion of FFAs by 34.52% and 40.32% respectively.